PENGARUH PEMBIAYAAN MODAL KERJA DAN FINANCIAL CONSTRAINTS TERHADAP KINERJA PERUSAHAAN - Yatazya Muzamil; Hersugondo Hersugondo (Jurnal Ekonomi Dan Bisnis, 2021)
The purpose of this study is to examine the relationship between working capital financing and financial constraints for a sample of 109 non-financial firms in Indonesia. The study is based on secondary financial data of 109 Indonesian non-financial companies obtained from Bloomberg, pertaining to a period of 5 years (2015-2019). This study employs Generalized Method of Moments (GMM) as techniques. The findings show that working capital financing has a positive effect on firm performance. Results of the study confirm the inverted U-shape relationship between working capital financing and firm performance. In addition, the authors also found that financial constraints have a simultaneous effect on firm performance. The regression results also show the indicators of financial constraints, size, growth, and current ratio have a positive effect on the firm performance. Meanwhile, asset tangibility, age, and leverage have a negative effect on firm performance